Діалектні вияви словозміни ойконімів у західнополіських говірках - Зінчук, Руслана Степанівна; Zinchuk, R. S. (Ужгородський національний університет, 2009)
Простежено діалектні вияви формотвірної системи ойконімів у західнополіських говірках, зауважено ряд архаїчних структур. Встановлено, що аналізовані оніми, зберігаючи як давні мовні явища, так і фонетико-морфологічні новотвори, типові для певного діалектного ареалу, можуть слугувати одним із джерел вивчення його специфічних рис. The dialectal cases of the form producing system of names of settlement in Western Polissyan dialects are traced, a number of archaic structures are observed. It has been pointed out that the onyms under consideration preserving the archaic lingual phenomena as well as new phonetico-morphological forms which are typical for a certain dialectal area, may serve as one of the sources of studing its specific features.
The dialectal cases of the form producing system of names of settlement in Western Polissyan dialects
Keywords: західнополіські говірки; словозміна; ойконім; граматична аналогія; флексія; Western Polissyan dialects; word modification; name of a settlement; grammatical analogy; flection